1998
DOI: 10.1097/00002060-199801000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Axonopathy in Mild to Moderate Peripheral Arterial Disease

Abstract: The effect of mild to moderate arterial occlusive disease on peripheral nervous system conduction was prospectively investigated in 18 subjects and 18 control subjects, aged 40 to 85 years. Experimental and control subjects underwent a thorough history and physical followed by vascular and electrophysiologic studies. The primary outcome measure was the sensory nerve action potential. Although 33% of the subjects with peripheral arterial disease had experienced paresthesias, the clinical evaluation of sensation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…These deficits appear related to the neuropathy and myopathy previously described by our group 24,11,2728 and others. 56,3133 Our work demonstrates that there are functional tests, including the maximal isometric plantar flexion test we are describing in this paper, that can measure and stratify the degree of impairment in the legs of patients with PAD. Such measurements can be used both as diagnostic tools to assess the severity of PAD in each individual patient but also to potentially predict and guide therapy depending on the patient’s presentation.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…These deficits appear related to the neuropathy and myopathy previously described by our group 24,11,2728 and others. 56,3133 Our work demonstrates that there are functional tests, including the maximal isometric plantar flexion test we are describing in this paper, that can measure and stratify the degree of impairment in the legs of patients with PAD. Such measurements can be used both as diagnostic tools to assess the severity of PAD in each individual patient but also to potentially predict and guide therapy depending on the patient’s presentation.…”
Section: Discussionmentioning
confidence: 94%
“…Myopathic fiber type shifting from Type II to I 2,9 and the neuropathy in PAD muscle that has been shown to decrease conduction velocities and amplitude corroborate this trend. 3133 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the nature of pain changes with the progress of limb ischemia, from nociceptive in character during the phase of intermittent claudication to neuropathic in character during CLI [13,14,15,16]. It is indicated that we are dealing here with sensory neuropathy [17,18]. Pain in CLI patients meets the criteria for chronic neuropathic pain [9].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms that explain these changes are complex and still require further examination, but a number of studies in human and animal studies suggest that impaired proteostasis (i.e., altered signaling pathways that regulate protein synthesis and degradation) plays a central role in muscle atrophy [60,61]. A dysfunctional peripheral nervous system, such as identified demyelination or focal denervation on the neuromuscular junction, will also likely stimulate the process of muscle atrophy and contribute to the weakness and functional impairment [62,63]. Skeletal muscle abnormalities also include capillary rarefaction and impaired microcirculation in PAD patients with IC and these findings are more obvious in people suffering from CLTI [59,64,65].…”
Section: Skeletal Muscle Pathology In Padmentioning
confidence: 99%